Articulación de una poética para la ciudad enmudecida en las crónicas de José Donoso - Ferrada Aguilar, Andrés (Revista Chilena de Literatura, 2014)
The article focuses on a selection of chronicles in which José Donoso provides a denaturalized image of the city of Santiago in the 1980s. By stressing a poetics of transformation, the author narrates a city that confronts the silence pervading its urban practices and neighbourhoods. Under this guise, Donoso’s writing tactically articulates a voice for the city that challenges both the homogeneity imposed by traditional renditions and the order of a contemporary oligarchy.